The Influence of the Physiotherapeutic Program on Selected Static and Dynamic Foot Indicators and the Balance of Elderly Women Depending on the Ground Stability - Matla, Joanna; Filar-Mierzwa, Katarzyna; Ścisłowska-Czarnecka, Anna; Jankowicz-Szymańska, Agnieszka; Bac, Aneta (International journal of environmental research and public health, 2021)
Seniors are a constantly growing group of people in many societies. It is necessary to develop physiotherapeutic programs to improve their mobility. The aim of this study was to assess the impact of the physiotherapeutic program conducted unstable ground on selected indicators of motor functions of elderly women. Sixty women (60-80 years) participated in the research. Group A (N = 20) underwent a 12-week physiotherapeutic program on stable ground, group B (N = 20) followed an exercise program on unstable ground, and group C (N = 20) (control group) had no therapeutic intervention. The effects of the therapy were assessed by using a FreeMed platform (foot load analysis) and a Biosway balance system. The results were compared using ANOVA (the one-way analysis), the Kruskal-Wallis test and also the post hoc tests (Tukey's test and the multiple comparison test). In group A, a statistically significant change was observed in the static test and balance assessment, in group B this was observed in the static and dynamic foot tests and balance assessment, in group C, no statistical significance was achieved. The authors' physiotherapeutic program had a statistically significant effect on changes in the balance and selected indicators of the motor functions of the examined people. Comparing the results before and after the therapy more improvement changes were noted in women training on an unstable ground compared to women training on a stable ground.
Keywords: stable ground; unstable ground; Female; Aged; Exercise Therapy; techniky fyzikální terapie; Physical Therapy Modalities; Exercise; Humans; ženské pohlaví; senioři; terapie cvičením; lidé; cvičení; posturální rovnováha; Postural Balance; seniors; physical activity